Controversy of Islamic Law on The Distribution of Inheritance to the Heirs of Different Religion - Yusuf, Andi Asdar (State Institute of Islamic Studies (IAIN) Palu, 2017)
The ability and willingness to have sufficient property is always desired by people because the generations that have enough supply of life is better than the begging ones. However, the ownership or transfer of property rights in Islam is clearly regulated through inheritance, sale, gifts, grants, endowments, alms, and other lawful means, such as loans and mortgages. The ownership or transfer of property through inheritance is an important part of Islam. Inheritance relationship between offspring was not easily done, both based on the particular culture and religion. Among the Hindus, especially in Bali, girls do not receive inheritance. The same also applies to Western society in England some time ago. In Padang-Muslim society, men do not receive it. In Javanese society, inheritance is divided equally, without differentiating boys and girls. Such inheritance is based on the cultural standards and anthropocentric paradigm (man as the center of everything). Interesting to be studied is the case in which Muslim whose parents or relatives are still non Muslims or live in a non Muslim state, when they died, the children are legally entitled to the inheritance of their parents or relatives, while in the hadith narrated in Bukhari and Muslim explicitly stated the prohibition of inheritance of different religion.